1997
DOI: 10.1097/00007632-199706010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-Term Outcome of Cervical Spinal Cord-Injured Patients Older Than 50 Years of Age

Abstract: The functional outcome of the person older than 50 years with a complete cervical cord injury is poor. Of the 14% who survived the first year, all required extensive attendant care, and no neurologic improvement was seen. The patient with an incomplete cord injury has an overall good outcome regarding ambulation and returning to home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 4 publications
1
21
1
Order By: Relevance
“…This rate of improvement was higher than rates reported by Alander et al, 9 in which none of the patients with complete cord injury improved, and all required extensive care. Fisher et al 19 concluded that the motor recovery does not occur below the zone of injury for patients with complete spinal cord injury, and Marino et al 20 suggested that the recovery of neurological deficit after spinal cord injury is dependent on the aetiology and the severity of the injury and so is the improvement in the motor scores.…”
Section: Spinal Cord Injuries In Elderly Patientscontrasting
confidence: 58%
See 1 more Smart Citation
“…This rate of improvement was higher than rates reported by Alander et al, 9 in which none of the patients with complete cord injury improved, and all required extensive care. Fisher et al 19 concluded that the motor recovery does not occur below the zone of injury for patients with complete spinal cord injury, and Marino et al 20 suggested that the recovery of neurological deficit after spinal cord injury is dependent on the aetiology and the severity of the injury and so is the improvement in the motor scores.…”
Section: Spinal Cord Injuries In Elderly Patientscontrasting
confidence: 58%
“…1,2,[5][6][7][8] Injuries are compounded by coexisting morbidities, reduced independence and poor tolerance of immobilization. [9][10][11][12] These problems can complicate the rehabilitation of elderly patients and health-care systems are facing challenges in effectively and efficiently treating the injuries of these patients. 1,2,7,13 We had noted an increasing number of elderly patients with spinal injury and had found difficulties in their rehabilitation and safe discharge because of the problems described above.…”
Section: Introductionmentioning
confidence: 99%
“…There were 12 paraplegics, 10 with thoracic and two with lumbar lesions. The mechanisms of cord insult were trauma (26), spinal arterio-venous malformation (2) and transverse myelitis (1). Analysis was by retrospective review of medical records.…”
Section: Methodsmentioning
confidence: 99%
“…The indications for insertion ( Figure 2) were for dysreflexic symptoms (15), high residual urine volumes and subsequent recurrent or persistent urinary tract infection (UTI) (17), for protection of the upper tracts (6) or to predict outcome following TUS (1). All stents ( Figure 1) were inserted under direct vision using a rigid (028T, 028TW, 045TW) or a flexible cystoscope (028SW).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation